Evaluation of Pantoea eucalypti FBS135 for pine (Pinus massoniana) growth promotion and its genome analysis - Song, Z.; Lu, Y.; Liu, X.; Wei, C.; Oladipo, A.; Fan, B. (Journal of applied microbiology, 2020)
Aims Pinus massoniana is one of the most widely distributed forest plants in China. In this study, we isolated a bacterial endophyte (designated FBS135) from apical buds and needles of P. massoniana. Investigations were performed to understand the effects of the strain on pine growth, its genomic features and the functions of the plasmids it carries. Methods and Results Based on its morphological features and 16S rRNA sequence, strain FBS135 was primarily identified as Pantoea eucalypti. We found that FBS135 not only promoted the growth of P. massoniana seedlings, but also significantly increased the survival rate of pine seedlings. The whole genome of FBS135 was sequenced, which revealed that the bacterium carries one chromosome and four plasmids. Its chromosome is 4 023 751 bp in size and contains dozens of genes involved in plant symbiosis. Curing one of the four plasmids, pPant1, resulted in a decrease in the size of the FBS135 colonies and the loss of the ability to synthesize yellow pigment, indicating that this plasmid may be very important for FBS135. Conclusions Pantoea eucalypti FBS135 has a genomic basis to be implicated in plant‐associated lifestyle and was established to have the capability to promote pine growth. Significance and Impact of the Study To the best of our knowledge, this is the first report that such a bacterial species, P. eucalypti, was isolated from pine trees and evidenced to have pine beneficial activities. Our results elucidate the ecological effects of endophytes on forest plants as well as endophyte–plant interaction mechanisms.